O cinema sem rua - Ribeiro, Vivian Codogno [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The project consists of a book-report on the street movie theaters in Brazil, which are increasingly scarce. Multiplexes are taking the market by several factors, including scheduling and directed to the blockbusters that malls provide security, which does not occur in street theaters, which have a more independent programming. The report will portray the film as a physical space and playful all the influence that the place provides, yet is losing its audience

O projeto consiste em um livro-reportagem sobre as salas de cinemas de rua no Brasil, que estão cada vez mais escassas. Os multiplex estão tomando conta do mercado por diversos fatores, inclusive pela programação direcionada para os blockbusters e pela segurança que os shoppings oferecem, o que não ocorre nos cinemas de rua, que apresentam uma programação mais independente. A reportagem retratará o cinema como espaço físico e toda a influência lúdica que esse ambiente possibilita e que, mesmo assim, está perdendo o seu público
Keywords: Cinema - Brasil; Cinema amador; Cinema experimental; Jornalismo e cinema; Motion pictures - Brazil